(untitled) (Fiep Bulletin - online, 2014)
The diagnostic evaluation in psychomotor domain is very important in PE settings. Research shows that the focus about student’s interests, abilities and needs precede teaching goals specification, and that expert teachers mobilize knowledge on student’s competences and compare with their teaching intentions to certify that students will be able to reach the proposed goals. The purpose of this research was to analyze the diagnostic evaluation and its influence on planning decisions of ’more’ and ’less’ effective PE teachers. The sample was 10 teachers, classified by effectiveness categories. The teachers were interviewed and the identification of diagnostics was accomplished through content analysis. The ’most’ effective teachers emphasized evaluation in specific learning domain (psychomotor) and the diagnostic of these teachers influenced in larger degree their planning decisions. The results show that the quality of diagnostic evaluation had strong impact on both planning and teaching effectiveness.